Varietal mixture effect on the disease incidence and severity of bacterial blight in rice - Sarker, Suvonkar; Rahman, Md. Atikur; Anwar, Md. Parvez; Hossain, Muhammed Ali (Journal of the Bangladesh Agricultural University, 2020)
Bacterial blight (BB) caused by Xanthomonas oryzae pv. oryzae is an important disease of rice in Bangladesh. The experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh-2202, Bangladesh during the period from July to December 2017. Two T. Aman (monsoon) rice varieties viz. Binadhan-13 and BRRI dhan49 were used in this study. The main objective of the study was to evaluate the disease incidence and severity of BB during the growing period considering spatial arrangement of alternate rows and hills with nine different ratios (1:0, 1:2, 2:1, 2:3, 3:2, 2:4, 4:2, 1:1, 0:1). The effect of varietal mixtures on combined grain yield was also observed in this experiment. Rice cultivation with the varietal mixture ratios of 2:1 (2 rows Binadhan-13 : 1 row BRRI dhan49) and 1:1 (1 row Binadhan-13 : 1 row BRRI dhan49) considering the spatial arrangement of alternate rows showed minimum disease incidence at 60 and 90 days after transplanting (DAT) respectively, whereas 2:1 mixture ratio was also reduced disease severity at 60 and 90 DAT compared to all other varietal mixtures ratios including sole cultivation of both the varieties. Disease incidence and severity of BB was also reduced by the spatial arrangement of alternate hills and the best mixture ratio was 2:1 (2 rows Binadhan-13: 1 row BRRI dhan49) for low disease incidence and severity at 60 and 90 DAT, whereas 1:1 ratio (1 row Binadhan-13 : 1 row BRRI dhan49) of hill orientation reduced disease incidence and severity at 60 and 90 DAT compared to some other treatments including sole cultivation. All the mixed culture, irrespective of mixture ratio and spatial arrangement, resulted in higher grain yield than sole culture yield. In case of alternate hill, the highest grain yield of 5.32 t/ha was recorded when Binadhan-13 and BRRI dhan49 were planted in 1:1 ratio, which was respectively 1.79 t/ha (50.56%) and 0.56 t/ha (11.74%) higher than sole culture yield of Binadhan-13 and BRRI dhan49. In case of alternate row arrangement, cultivation of Binadhan-13 and BRRI dhan49 in 1:1 ratio resulted in the maximum grain yield of 5.22 t/ha which was respectively 1.69 t/ha (47.7%) and 0.46 t/ha (9.6%) highr than Binadhan-13 and BRRI dhan49 sole culture yields. Thus cultivar mixture confirms reduced incidence and severity of BB and rice yield advantage over sole culture. J Bangladesh Agril Univ 18(2): 354–361, 2020 https://doi.org/10.5455/JBAU.76259